Analisa Lapisan Keras (Bedrock) dengan Menggunakan Metode Seismik Refraksi - Utami, Binar; Fahruddin, Fahruddin; Siregar, Simon Sadok (Lambung Mangkurat University Press, 2009)
Each region generally has a condition of various land surface, usuallyused as information for making a geological map of the regions, but theinformation can not provide a real illustration of the depth of the hard layer(bedrock) found in the area. Thus, to determine the depth of the bedrock as theinitial information exploited for the region of Banjarbaru more, then done bymeasuring the depth of the bedrock by seismic refraction. Soil has severalcompiler layers, the deeper layer from surface is denser and each layer hasdefferent characteristics. The nature used in this research is the difference of thespeed to creep the seismic waves on each layer. By creeping the seismic waves,the information of undercoat surface is obtained depend on the speed increeping seismic waves. To find out the speed and types of layers under the soiland to know the depth of the bedrock in the region are done by using seismicequipment refraction, by initial assumption that bedrock usually is found in therelatively shallow depth in the region of Banjarbaru. From the results of the datasampling done by measuring the length of the track 72 meters and thenprocessed by using the software winsism 10 bedrock was found on the yard ofengeniring faculty Unlam Banjarbaru in depth around 6-15 meters, in the speedof spreading waves in the range of 2800-3200 (m/s) and there is nappe layer(top soil) of the seismic waves creeping velocity 300-400 (m/s) and a much watercontent-thinner layer spreading speed of seismic wave in the range of 1400-1600(m/s).